Experimental measurements for free Space Optical Links - White-Hernandez, Brian David (Instituto Tecnologico de Costa Rica. Escuela de Ingenieria Electronica., 2007)
The project described consists on the development of a compact size Bit Error Rate Tester(BERT), for the Free Space Optical(FSO) communications system that is being developed on the photonics laboratory of Politecnico di Torino(Photonlab), located in Turin, Italy. The BERT was based on a Xilinx Virtex II-PROTM, this FPGA was chosen because of the high speed serializer interface, that allowed the implementation of a 2.5Gb/s pattern generator and error detector. The software was programmed in Micrsoft c Visual C#, to implement the interface with the user, also it's capable of creating a .log file with the BER test results in order to perform a post processing analysis of the system's BER evolution in time.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2007.
Keywords: Instituto Superiore Mario Boella; Politecnico di Torino; Óptica espacial; Comunicación; RocketIO; BERT; Virtex II-PRO; PRBS; Visual C#